PENINGKATAN KINERJA UMKM JANGGELAN DI KABUPATEN PACITAN MELALUI INTRODUKSI TEKNOLOGI PRODUKSI DAN MANAJEMEN KEUANGAN - Wiwit Rahayu; Dwi Ishartani; Nuning Setyowati (LPPM UNS, 2016)
”Janggelan” (Mesona palustris BI) that known by the name of Black Cincau is one of the plant species in Indonesia are grown widely in Pacitan, especially in Bandar sub district. “Janggelan” in Bandar subdistrict has good prospects to be developed because a lot of production and marketing is widespread. This opportunity was captured by residents in the “Jeruk Village”, Mr. Suyanto who processing wet “janggelan” into dry “janggelan” with the business name